PENGELOLAAN PROGRAM BIMBINGAN KEIMANAN DAN KETAKWAAN (BIMTAQ) DALAM MEMBENTUK DISIPLIN SISWA DI SMP ISLAM Al-FATIH - Dara Avira; Amiruddin Siahaan (Jurnal Manajemen Pendidikan, 2026)
One strategic effort in fostering students' spiritual development is the Guidance for Faith and Piety (BIMTAQ) program. This program is designed to instill Islamic values ​​through various activities, such as congregational prayer, Quran reading, religious instruction, and the development of good morals in daily life. This study aims to examine how the Faith and Piety Guidance (BIMTAQ) program is managed to foster student discipline at Al-Fatih Islamic Junior High School Plus. The method used is a qualitative approach with a descriptive research style, allowing researchers to understand the phenomenon in depth according to the conditions on the ground. Data collection was conducted through direct observation, in-depth interviews, and documentation. The research subjects included the principal, teachers, BIMTAQ instructors, and students. The results indicate that the implementation of the BIMTAQ program has followed the four main management functions: planning, organizing, implementing, and supervising. This program has proven to have a significant impact on fostering student discipline, particularly in terms of punctuality, worship, and daily behavior. However, several obstacles remain in its implementation, such as limited time allocation and inconsistency in some students' participation in activities.